Proceedings of the 2004 Congress on Evolutionary Computation (IEEE Cat. No.04TH8753)
DOI: 10.1109/cec.2004.1331109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of noise on the performance of cultural evolution in multi-agent systems

Abstract: Abstract-This paper examines the effect of the addition noise to the cultural learning process of a population of agents. Experiments are undertaken using an artificial life simulator capable of simulating population learning (through genetic algorithms) and lifetime learning (through the use of neural networks). To simulate cultural learning, (the exchange of information through non-genetic means) a group of highly fit agents is selected at each generation to function as teachers which are assigned a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
2
0
0
1
Order By: Relevance
“…An experiment conducted in our previous work [21] confirmed that small levels of noise introduced into the communication process improved both the formation of a shared lexicon and agent performance.…”
Section: Cultural Learningsupporting
confidence: 70%
“…An experiment conducted in our previous work [21] confirmed that small levels of noise introduced into the communication process improved both the formation of a shared lexicon and agent performance.…”
Section: Cultural Learningsupporting
confidence: 70%
“…In previous work by Denaro and Parisi (1996), it was suggested that the addition of noise to a teacher's verbal output could enhance a population's ability to retain culturally acquired information. Experiments conducted in our previous work (Curran & O'Riordan, 2004) confirmed that small levels of noise introduced to the communication process improved both the formation of a shared lexicon and agent performance.…”
Section: Cultural Learningsupporting
confidence: 54%
“…En [113], se considera la teoría de la cognición distribuida para establecer un modelo conexionista sobre el desarrollo cultural de símbolos lingüísticos. En [114] se emplea dicho modelo, en un algoritmo genético híbrido, con aprendizaje individual y cultural. Los mejores individuos en cada generación funcionan como tutores, al comunicar sus propias "verbalizaciones" sobre el medio ambiente a pupilos con la capacidad de imitarlas.…”
Section: Evolución Cultural Con Neuro-agentesunclassified